STAR WARS ENCYCLOPEDIA OF STARFIGHTERS AND OTHER VEHICLES - Walker, Landry Q.; Jones, Matt; Nesworthy, Lauren (London : Dorling Kindersley Limited, 2018)
Learn all about over 200 of your favourite Star Wars vehicles, from the A-wing to the Y-wing. Want to know how the Millennium Falcon made the Kessel Run in such a short distance? Not sure what type of craft Slave I is? From the swamps of Kashyyyk to the deserts of Jakku, from inner-city Coruscant to the vastness of hyperspace, Star Wars Encyclopedia of Starfighters and Other Vehicles will show you the right craft for the job. Covering vehicles from across every Star Wars movie, as well as The Clone Wars and Star Wars: Rebels.
includes index
Keywords: Space vehicles in motion pictures -- Juvenile literature; Star Wars films -- Juvenile literature -- Miscellanea; Space warfare -- Juvenile literature